2015
DOI: 10.3892/or.2015.4485
|View full text |Cite|
|
Sign up to set email alerts
|

FAM172A modulates apoptosis and proliferation of colon cancer cells via STAT1 binding to its promoter

Abstract: In our previous study, low expression of FAM172A protein was found in colon cancer tissues. This research was planned to explore the functions of FAM172A gene and examine the mechanisms of its transcriptional regulation. Firstly, flow cytometry showed that FAM172A inhibited proliferation and promoted apoptosis and differentiation of colon cancer cells. Then through continuous truncation, we identified the minimal functional promoter region of FAM172A. Subsequently, we found that STAT1, as a transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
16
1
1
Order By: Relevance
“…As a protein of 416 amino acid, FAM172A belongs to the UPF0528 family and its protein-coding gene is located in human chromosome 5 (9). Our previous research showed that FAM172A expression had a lower expression in CRC tissues of patients with metastasis compared with CRC tissues of patients without metastasis (11). However, relevant studies of FAM172A and its more unknown functions in CRC are still scarce.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As a protein of 416 amino acid, FAM172A belongs to the UPF0528 family and its protein-coding gene is located in human chromosome 5 (9). Our previous research showed that FAM172A expression had a lower expression in CRC tissues of patients with metastasis compared with CRC tissues of patients without metastasis (11). However, relevant studies of FAM172A and its more unknown functions in CRC are still scarce.…”
Section: Discussionmentioning
confidence: 97%
“…Our prior studies showed that overexpression of FAM172A inhibited the migrational capability and cell invasiveness of CRC cell lines by suppressing the expression of MMPs (11). To further explore the biological functions of FAM172A regulated by miR-27a in LoVo and SW480 cell lines, we determine the effect of miR-27a on cell poliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cui et al has also reported in a work with a colorectal cancer model that FAM172A might inhibit the growth and invasion of colorectal cancer cells and the mechanism involved activation of ERS signaling [24]. Qian et al demonstrated that FAM172A was upregulated by the STAT1 transcription factor and also downregulated, thus modulating apoptosis and the proliferation process of colon cancer cells (human LoVo and SW480 cells) [33]. Similar in line with the results in our studies, Wang and Tai demonstrated that high expression levels of MAPK, phosphorylated MAPK, and phosphorylated MEK1/2 were found in tumors of HCC patients [16].…”
Section: Discussionmentioning
confidence: 93%
“…3E), and F ( Effect of tea tree oil on inflammatory factors and apoptotic factors in the LPS-induced mastitis model TNF-α and IL-6 are inflammatory factors related to the inflammatory response (20). STAT1 is related to apoptosis (21). Compared with the blank group, TNF-α and IL-6 were expressed more than 15 times higher in response to LPS treatment at a concentration of 200 µg/ml.…”
Section: Effect Of Tea Tree Oil On Lps-induced Bmecsmentioning
confidence: 87%